The Hidden Struggle An Enquiry into the Nature of Poverty of Women, as manifest in their Household Survival - Smith, Mithrani Sureka Fernando (My University, 2010)
The woman, in her poverty, is seen to labour and struggle for her household survival. It is an eternal phenomenon. We see her within pages of history, we see her in modem reality. Her continuing presence remains a challenge to development. Poverty has long embraced Development as a remedial measure, but its rising presence remains a tenacious problem almost globally. In emerging study and literature it is graphically argued that women represent a disproportionate and increasing share of the world's poor. Scholars look within the development process, and perceive that- Macro-level economic policies have impacted with adversity upon women and families, specially those in poverty. They further draw attention to the fact that restructuring of the economy has driven women into insecure employment, unprotected home based production and dangerous working conditions. They see the diminishing social security systems impact gravely upon women's daily lives, heightening inequities in their quality of life: In nutrition, health care, education and in their opportunity to lead a full and productive life. Women's deeper experience of poverty continues; clearly manifest in their exclusion, lack of access to decision making power, freedom of thought, legal protectionand rights; access to and control over resources in household; rising trends in domestic instability and violence, physical insecurity, conflict. Arising from long entrenched gendered structures, they remain strong socio-cultural impediments to women's development, make their household survival a hidden struggle. Thus, the nature of poverty women experience hold diverse interconnected manifestations; economic,social, cultural, which lead to deeper human manifestations; often rooted xv "1 in history, acquiring deeper complexity in modernity, these shadow her path to development. Thus, the objective of our study is to examine the diverse manifestations of poverty women experience in their household survival; their economic, social, cultural, human dimensions and to grasp its impact upon lives of women, their families and upon development as a whole. Our search into a vast canvas of literature brought forth illuminating findings: It revealed the deep historical roots to women's gender based poverty, the hierarchical structures which yet prevail, perpetuating woman's subordination; it further brought forth women's grave inequities in several dimensions: income, employment opportunity, access to means of production, food security for survival. It revealed grave relative deprivation in education- the prime tool of social affIrmation and development; in health care, which gravely endangers woman's prospects for life itself. It brought forth the many faces of woman's absolute poverty, her constant struggle for household survival. A poverty deeply entrenched in culture, beheld the spiral perpetuate through the life of the girl child, first within the domestic domain, then reaching beyond to the wider society. More profound were the hidden manifestations, entrenched within a culture of silence. Searching within the Development process itself, women's marginalization herein was manifest; clear in arenas where women's efforts for household survival are fundamental: agricultural production,the environment, industrial production, the informal economy. It brought to light some of the causes for the continuation of women's poverty, despite the forcesof developmen